The Evangelical Alliance's Commitment to Religious Liberty in Austria during the Second Half of the 19th Century - Hinkelmann, Frank (Evangelical review of theology, 2021)
Even in the late 19th century, being an evangelical Protestant in some parts of western Europe was dangerous. Drawing extensively on original documents, this article describes global evangelicals' determined efforts to secure religious freedom for their compatriots in Austria.